EXPERIMENTAL STUDY OF MECHANICAL PROPERTIES AND CORROSION RATE OF LOW CARBON STEEL AISI 1020 RESULTING FROM LOW PRESSURE GAS CARBURIZING - Audrey, Reinaldo Evan; Setyarini, Putu Hadi; Sugiarto, Sugiarto; Sholikin, Atfalus (International Journal of Mechanical Engineering Technologies and Applications, 2025)
Within the realm of demanding marine operations, tugboat chain sprockets have a vital function in guiding and controlling giant ships. Marine conditions provide considerable obstacles for chain sprockets, which are commonly constructed from low-carbon steel for their cost-effectiveness and mechanical appropriateness. One such problem is corrosion, which can result in material failure. AISI 1020, a low-carbon steel containing around 0.2% carbon, provides exceptional toughness and resistance to corrosion, especially for applications in mining and oil platforms. The poor corrosion resistance of the material, worsened by exposure to air and salt in saltwater, requires a remedy. In order to enhance wear and corrosion resistance, low-pressure gas carburizing (LPGC) is suggested as a method to augment surface hardness and establish a durable oxide layer. This approach provides benefits in managing carbon penetration with less distortion and environmental effect as compared to conventional carburizing methods. Evidence indicates that low-pressure carburizing increases the flow of hydrocarbon gas, which in turn promotes even diffusion of carbon, thereby enhancing the distribution of hardness. The work explores the efficacy of LPGC in improving the operating longevity and efficiency of chain sprockets in marine environments. Its objective is to investigate how carbon augmentation via LPGC changes the steel microstructure, enhances corrosion resistance, and increases tensile strength. Materials utilized were AISI 1020 low-carbon steel plates. They were treated by regulating temperature fluctuations and specific durations of holding. Subsequently, the plates underwent measurements of Micro-Vickers hardness, tensile strength, SEM-EDX analysis, and corrosion using a Tafel Extrapolation. Results indicate a substantial rise in hardness in carburized specimens, with the best result achieved at 950°C for 60 minutes. According to the study, LPGC successfully enhances the mechanical and anti-corrosive characteristics, therefore prolonging the lifespan of nautical components and maximizing their performance under demanding circumstances.